2022
DOI: 10.3390/agriculture12081187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen and Phosphorus Fertilization on Photosynthetic Properties of Leaves and Agronomic Characters of Alfalfa over Three Consecutive Years

Abstract: The present study aimed to investigate the nitrogen (N) and phosphorus (P) fertilization of continuous addition effects plant biomass, the physiological properties of leaves and the antioxi-dant enzyme activities of alfalfa (Medicago sativa L) in the northern Xinjiang region; including the no fertilization (CK), nitrogen fertilization (N, 120 kg·ha−1), phosphorus fertilization (with low amount of N) (P, 100 kg·ha−1 P and 23.5 kg·ha−1 N) and combined nitrogen and phosphorus fertilization (NP, 120 kg·ha−1 N and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…A schematic representation drawn from this present work illustrates how the N application might have mediated the changes to improve the overall performance of peppermint cultivars ( Figure 16 ). The results on the improvement in size and density of stomata and trichomes due to N application corroborate with the findings of [ 36 ] on Tagetes minuta L. and [ 37 ] on Medicago sativa L.…”
Section: Discussionsupporting
confidence: 87%
“…A schematic representation drawn from this present work illustrates how the N application might have mediated the changes to improve the overall performance of peppermint cultivars ( Figure 16 ). The results on the improvement in size and density of stomata and trichomes due to N application corroborate with the findings of [ 36 ] on Tagetes minuta L. and [ 37 ] on Medicago sativa L.…”
Section: Discussionsupporting
confidence: 87%
“…Chlorophyll content exerts a direct influence on photosynthesis and the generation of photosynthetic products [28]. Several factors affect photosynthesis, with nitrogen (N), phosphorus (P), and potassium (K) playing pivotal roles [29]. Furthermore, previous studies have demonstrated a positive correlation between nitrogen concentrations and the photosynthetic carbon assimilation rate of leaves, thereby influencing the plant's photosynthetic capacity [30,31].…”
Section: Effects On Photosynthetic Pigmentsmentioning
confidence: 99%
“…These rhizobia can convert atmospheric N into plant available forms. However, despite the N fixing capabilities of these rhizobacteria, alfalfa may experiences N deficiency, due to inadequate soil nutrients ( Zielewicz et al., 2023 ) salt stress ( Wan et al., 2023 ), drought ( Liu et al., 2018 ), and other factors, which ultimately reduce plant growth, yield, and quality ( Zhao et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%